Does footwear affect articular cartilage volume change after a prolonged run?. (11th November 2019) - Bratke, Grischa; Bruggemann, Gert‐Peter; Willwacher, Steffen; Mählich, Daniela; Trudeau, Matthieu B.; Rohr, Eric; Weir, Gillian; Maintz, David; Hamill, Joseph
Abstract : The aim of this study was to investigate knee intra‐articular cartilage volume changes after a prolonged running bout in three footwear conditions. Twelve participants performed 75‐minute running bouts in the three footwear conditions. Before and after each running bout, magnetic resonance imaging (MRI) scans were obtained using a high‐resolution 3.0 Tesla MRI. Three‐dimensional reconstruction of the cartilage plates of the patella, the femur, and the tibia was created to quantify cartilage volume change due to the 75‐minute running bout. Three‐dimensional biomechanical data were also collected using an integrated motion capture and force treadmill system. There were no statistically significant differences among shoe conditions for all anatomical regions. However, significant cartilage volume reductions at all anatomical sites were observed after the 75‐minute running bout in each footwear condition. These data suggest that the intra‐articular knee cartilage undergoes a significant reduction in cartilage volume during a prolonged run that may indicate an increase in joint loading. There was a considerable variation in cartilage volume between participants across footwear conditions indicating an individual cartilage volume response to footwear. An individualistic approach to footwear recommendations may help in minimizing this change in cartilage.